(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was the one of verify as the Sporty Federations of State of Amazon, specialized in collective sports (basketball, volleyball, five-a-side football, soccer and handball) determined the objectives of the competitions of the smaller categories, verify the rules adaptations of game regarding the adults and to identify the forms of used disputes. It concluded that: (i) Just three Federation (volleyball, basketball and soccer) defined in their regulations the goals that intended to reach with accomplishment of the minors competitions; (ii) there are no difference in time duration of the games, with exception in the of the handball, the others competitions are identical to the of the adults; (iii) there is variability in the age in which initiate the competitions of smaller and finally (iv) the disputes forms of the infantile and juvenile competitions, of all the searched modalities, are reproductions of the adults competitions and the children have ages below those precocious by literature.